ANALISIS BANJIR BANDANG DENGAN MENGGUNAKAN DATA CITRA SATELIT DI KABUPATEN LUWU UTARA (STUDI KASUS 13 JULI 2020) - Rino Wijatmiko Saragih (JURNAL PEMBELAJARAN FISIKA, 2021)
Flash floods that hit parts of South Sulawesi on July 13, 2020, left 36 people dead, 18 people lost, 40 people missing, 58 injured, and a total of 14,483 people were affected. Around 14,000 people were evacuated to safer locations due to not having a home to live in. The disaster was caused by heavy rains. One of the areas affected was North Luwu. This phenomenon needs to be done research so that people can overcome the possibility of disasters that might occur. Air pressure and air temperature for 2 days before the occurrence of flash floods have the same relative patterns and anomalies occurred on the day of the incident. This research uses satellite image data interpretation method by processing the Himawari-8 infrared channel data and compared with rainfall data from the Andi Jemma meteorological station in North Luwu Regency on July 13, 2020. Interpretation and analysis of satellite imagery data shows the growth of strong convective clouds has the potential to cause rain in North Luwu around 07.00 UTC. So it was concluded that during a flash flood, unstable atmospheric conditions and the presence of Cumulonimbus (CB) cloud cover in the North Luwu region.